WORK OF ABUL YUSR PAZDAVI “USULU-D-DIN” AND ITS PLACE IN THE DEVELOPMENT OF THE TEACHING OF MOTURIDISM - Sodikov Jurabek Sobirboyevich (Modern American Journals, 2025)
This article explores the life and scholarly activity of one of the renowned scholars of Transoxiana, Abu al-Yusr Muhammad ibn Muhammad ibn Husayn ibn ‘Abd al-Karim ibn Musa al-Pazdawi. It provides an overview of his teachers, prominent students, and academic legacy, with a particular focus on his seminal theological work Usul al-Din. The article highlights the thematic content and distinct characteristics of the work, demonstrating how al-Pazdawi addressed doctrinal issues from a Maturidite perspective. Furthermore, it examines his views on the legitimacy and importance of studying the science of kalām. Selected theological issues raised in Usul al-Din are analyzed, and their relevance to contemporary thought is illustrated through specific examples. The text also investigates al-Pazdawi’s position toward another prominent figure of Ahl al-Sunna, Abu al-Hasan al-Ash‘ari, and his followers, with references to passages in which al-Pazdawi comments on them.
Keywords: Al-Pazdawi, Usul al-Din, Samarqand school of kalām, Hans Peter, Ahl al-Haqq, jawhar, ‘arāḍ, tadbīr.